Symbolism of sacred and profane animals in the Quran - Anas Ahmadi (Faculty of Social and Political Science, Universitas Airlangga, 2020)
The story of animal symbolism is associated with knowledge and wisdom. This is in order to be used as an example by humans as a valuable lesson. Humans can learn ethics from fables. In the modern view, the symbolism of animals in relation to the issue of eco-psychology has become a trending topic. This study aims to explore the symbolism of sacred and profane animals in the Quran through a hermeneutic-anthropological perspective. This study used a qualitative-descriptive method by describing the data narratively. The data analysis techniques used in this study are hybridization techniques. First, there is reciting the verses (hermeneutical-anthropological) in the Quran can be either universal or particular. Second, there is identifying the passages that relate to animals, whether real pets or unreal ones (symbolism). Third, there is the classification of the animals associated with the pattern of binary oppositions, and the Quran in the context of mytheme (unit of myths) and cheritheme (unit of the story). Fourth, there is the search for collective mediation functions for the community supporters who are in the Quran - mytheme and cheritheme animals. The findings of this study are that: 1) animal symbolism in the Quran appears in the form of either dyadic or triadic and 2) the symbolism of animals the Quran shows that animals in the Quran have a collective mediating function for the supporting community,i.e. a) animals as intermediaries towards holy people (through sacrifice); b) animals as medicine/human health; and c) animals as protectors. The conclusion of this study shows that animals in the Quran appear in both real and symbolic form.